Information assistance systems as preventive mediators between increasing customization and mental workload. - Bläsing, Dominic; Hinrichsen, Sven; Wurm, Susanne; Bornewasser, Manfred; Brandl, Christopher; Nitsch, Verena (Work, 2022)
BACKGROUND: The future of work in Germany is shaped by megatrends like globalization, automatization, digitization, and the demographic change. Furthermore, mass customization and the increasing usage of AI even in manual assembly offers new opportunities as well as it creates new challenges. OBJECTIVE: The trend towards mass customization in turn leads to increased complexity in production, which results in additional mental workload. This effect will continue in the foreseeable future. METHOD: Especially for small and medium sized companies, the backbone of Germany's economy, automatization and Human-Robot-Collaboration will take time to develop. Information assistance systems are and will be a bridging technology to help organizations to manage increasing complexity and the mental workload of their employees to not only boost productivity but also keep their workforce healthy. The ongoing demographic change further underlines the need to use information assistance systems to compensate possible age-associated deficits, but also keep older employees committed to their work and avoid effects of disengagement or disenfranchisement through participatory ergonomics. RESULTS: Information assistance systems can only develop their inherent potential if they are designed to support employees of varying age, competence levels, and affinity for technology. Participatory development and early engagement are key factors for an increased acceptance and usage of the systems as well as the individualization to make it suitable for each individual employee. CONCLUSION: Expanding the functionalities to an adaptive assistance system, using physiological correlates of mental workload as an input, is conceivable in the future.